(untitled) (Research, Society and Development, 2021)
Introduction: The pregnancy period is evidenced by changes, which include physical, psychological and social changes in pregnant women. Objective: To verify anxiety and depression in the COVID-19 pandemic context and the relationship with the defense mechanisms of pregnant women so that coping strategies with professional assistance are developed. Method: Cross-sectional study with descriptive design, quantitative analytical approach, with correlation between variables, developed in a specialized maternal and child center and in the emergency obstetric sector of a hospital, both in the São Paulo countryside. Sixty-one pregnant women participated in the study, 30 from specialized maternal and child center and 31 from the obstetric emergency, aged 18 years or over. Data were collected through two questionnaires, one with sociodemographic data and the other with open and closed questions about positive and negative defense mechanisms. To assess symptoms of anxiety and depression, the Hospital Anxiety and Depression Scale was used, data that were analyzed descriptively and inferentially. Results: It was found that 29.51% of pregnant women had symptoms of anxiety and 24.59% symptoms of depression. Of the pregnant women who presented depression, 66.67% were in the obstetric emergency. It was found that 14.75% said they consumed alcohol or illicit drugs during the COVID-19 pandemic context, 45.90% of the pregnant women did not perform physical activity during the pandemic period and 49.18% had difficulty sleeping. Conclusion: The results of the study show that part of the pregnant women have a situation of vulnerability related to impaired mental health and marked changes in routine in the current pandemic period.